EF24 and RAD001 potentiates the anticancer effect of platinum-based agents in human malignant pleural mesothelioma (MSTO-211H) cells and protects nonmalignant mesothelial (MET-5A) cells. (February 2015) - Onen, HI; Yilmaz, A; Alp, E; Celik, A; Demiroz, SM; Konac, E; Kurul, IC; Menevse, ES
The most widespread neoplasm of the pleura is malignant pleural mesothelioma (MPM) with low prevalence rate. The mechanistic target of rapamycin signaling pathway, inhibited by RAD001, was shown to be deregulated in MPM development and considered a novel target for the MPM therapy. The EF24, a curcumin analog, also affects several signaling pathways and kills cancer cells as a single agent or in combination with classical drugs. We aimed to evaluate possible effects of RAD001, EF24, cisplatin, and oxaliplatin treatments on both malignant pleural mesothelioma (MSTO-211H) and nonmalignant mesothelial (Met-5A) cell lines. The effects of the agents on MSTO-211H and Met-5A cells were evaluated in terms of cell viability, cytotoxicity, DNA synthesis rate, quantitation of apoptotic DNA fragmentation, and cleaved caspase 3 levels. Moreover, quantitative messenger RNA (mRNA) analysis of apoptotic ( CASP9 ) and antiapoptotic ( BCL2L1 and BCL2 ) genes were also performed. We found that both EF24 and RAD001 alone treatments decreased only MSTO-211H cell viability, but cisplatin and oxaliplatin affected both cell lines. Pretreatment with EF24 or RAD001 followed by cisplatin increased the effects of cisplatin alone application. EF24 and RAD001 pretreatment decreased DNA fragmentation rate when compared with cisplatin alone treatment in Met-5A cells. Sequential treatments resulted in a significant increase of CASP9 mRNA expression in MSTO-211H cells but not in Met-5A cells. Our preliminary results suggest that pretreatment with EF24 or RAD001 may reduce cytotoxic effect of cisplatin on nonmalignant mesothelial cells and increase cell death response of MPM cells. Further analyses using animal models are needed to confirm these findings in vivo.